In vitro establishment of lytic and nonproductive infection by herpes simplex virus type 1 in three-dimensional keratinocyte culture. - Syrjänen, S (1996)
The F strain of herpes simplex virus type 1 (HSV-1) was tested for its ability to produce lytic or nonproductive infection in squamous epithelial cells cultured in a three-dimensional organotypic tissue culture. For the tissue culture, we used HaCat cells (immortalized skin keratinocytes) and normal fibroblasts derived from the skin. The cultures were infected with HSV-1 (5 PFU) either when the epithelial cells had grown as a monolayer with a confluence of 80% on the collagen fibroblast gel or 30 min after lifting of the epithelial cells into the air-liquid interface. The cultures were collected 1 week after inoculation. Typical cytopathic effects of HSV infection (ballooning and reticular degeneration with multinucleate giant cells) were seen only in those cultures in which the epithelial cells were infected before lifting. The presence of HSV was confirmed by DNA and RNA in situ hybridization and PCR. No morphological changes were found in cultures infected after lifting into the air-liquid interface. No infectious virus was recovered either from cells or culture supernatant. However, these cultures were positive for HSV DNA on PCR and showed expression of the LAT gene by in situ hybridization and Northern blot (RNA) hybridization. The present results indicate that both nonproductive and lytic HSV infection can be produced in vitro and the outcome of the infection depends on the time of viral inoculation in relation to epithelial maturation.